Refugees from Ukraine value job opportunities over welfare - Joop Adema; Lasha Chargaziia; Yvonne Giesing; Panu Poutvaara (Proceedings of the National Academy of Sciences, 2025)
Understanding refugees’ destination choices is key to designing appropriate policies, but little is known about this beyond correlational patterns and the effects of isolated policy changes. To derive causal evidence on how destination country characteristics affect refugees’ destination choices, we conducted a forced-choice conjoint experiment among 3,348 Ukrainian refugees across Europe. In the survey experiment, refugees repeatedly chose between two hypothetical countries that varied on eight relevant attributes. Ukrainian refugees are uniquely suited to study the relative importance of different host country attributes as they have the right to choose in which member state of the European Union they apply for temporary protection. We find that job opportunities are a much stronger driver of destination choice than social assistance. A one SD increase in average wages makes it 16.4 percentage points more likely that the country is chosen in the survey experiment, while a corresponding increase in social assistance increases the probability of the country being chosen by only 4.5 percentage points. The ease of finding a job matching one’s qualifications is valued even more than having friends or family and knowing the language of the country. We also find strong sorting in that respondents who value knowing the language and job opportunities in our survey experiments are also more likely to have settled in countries where this is the case. Conjoint experiments can be used to assess refugees’ anticipated migratory responses to proposed policy changes.